Tertawa Dalam Perspektif Hadis Nabi SAW - Aziz, Muhammad Abdul; Junaidi, Junaidi (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
Laughter is an activity that is often found in various situations and conditions, especially in meetings and gatherings in social relationships. This is because human nature which tends towards happiness and pleasure is the driving force for this expression of laughter. However, in the hadith the Prophet S.A.W. forbids us from laughing excessively. . The aim of this research is to analyze the positive and negative impacts of laughter. The research method used was thematic research method (Maudhu'i). The data sources that the author uses in this research include primary data and secondary data. The data collection technique created by the author by first searching for what data is needed in discussing this thesis is thematic research (maudhu'i). Collecting hadiths related to analysis of hadiths regarding the prohibition of laughing, then looking at the Islamic scholars' syarah regarding these hadiths. The results of this research show that in reality nowadays people often laugh too much. Therefore, in Islam there are separate rules regarding laughter. In the hadith, it is explained that laughter that is permissible is laughter that only shows the molars or just smiling, while laughter that is prohibited in the hadith is laughter that causes a loud sound.